Prospective surveillance pilot of rivaroxaban safety within the US Food and Drug Administration Sentinel System. Issue 3 (10th January 2018) - Chrischilles, Elizabeth A.; Gagne, Joshua J.; Fireman, Bruce; Nelson, Jennifer; Toh, Sengwee; Shoaibi, Azadeh; Reichman, Marsha E.; Wang, Shirley; Nguyen, Michael; Zhang, Rongmei; Izem, Rima; Goulding, Margie R.; et al.
Abstract: Purpose: The US Food and Drug Administration's Sentinel system developed tools for sequential surveillance. Methods: In patients with non‐valvular atrial fibrillation, we sequentially compared outcomes for new users of rivaroxaban versus warfarin, employing propensity score matching and Cox regression. A total of 36 173 rivaroxaban and 79 520 warfarin initiators were variable‐ratio matched within 2 monitoring periods. Results: Statistically significant signals were observed for ischemic stroke (IS) (first period) and intracranial hemorrhage (ICH) (second period) favoring rivaroxaban, and gastrointestinal bleeding (GIB) (second period) favoring warfarin. In follow‐up analyses using primary position diagnoses from inpatient encounters for increased definition specificity, the hazard ratios (HR) for rivaroxaban vs warfarin new users were 0.61 (0.47, 0.79) for IS, 1.47 (1.29, 1.67) for GIB, and 0.71 (0.50, 1.01) for ICH. For GIB, the HR varied by age: <66 HR = 0.88 (0.60, 1.30) and 66+ HR = 1.49 (1.30, 1.71). Conclusions: This study demonstrates the capability of Sentinel to conduct prospective safety monitoring and raises no new concerns about rivaroxaban safety.